Novel Proton-Conducting Polymer Electrolytes Based on Poly(Vinylidene fluoride-co-hexafluoropropylene)–Ammonium Thiocyanate. (11th December 2016) - Selvakumar, K.; Kalaiselvimary, J.; Rajendran, S.; Prabhu, M. Ramesh
ABSTRACT: The polymer electrolytes composed of poly(vinylidene fluoride- co -hexafluoropropylene) with various concentration of ammonium thiocyanate salt have been prepared by solution casting technique. The complex formation between polymer and dissociated salt has been confirmed by X-ray diffraction analysis and Fourier transform infrared spectroscopy. The highest conductivity has been found to be 6.5 × 10 −3 S cm −1 at 343 K for 25 wt% ammonium thiocyanate. The temperature-dependent conductivity of polymer electrolyte follows Arrhenius hopping relation. Thermogravimetric analysis has been used to ascertain the thermal stability of the polymer electrolytes. Atomic force microscopy analysis predicts the roughness parameter of the sample with higher conductivity. GRAPHICAL ABSTRACT: